Exploring the Impact of Youtube on Public Administration Students"™ Communication Skills - Sholikhi, Fu'ad; Zuliansadewi, Sikha (Journal of English Education Program, 2024)
The transition from traditional classroom-based language learning to online learning outside the classroom particularly in response to the global Covid-19 pandemic has transformed the way educators and learners approach teaching and learning activities. This research provides insights into the views of twelve Public Administration students on the use of YouTube videos for learning English digitally outside the classroom in their speaking class. The investigators utilized a qualitative research approach, conducting thorough in-depth interviews and observations. The initial step in analyzing the data of Public Administration students"™ perception was data reduction, which was subsequently followed by additional data reduction and the drawing of conclusions. The results revealed that many of the participants concurred that YouTube had a substantial impact on their speaking class. Despite a small number of students encountering network-related issues, such as quota limitations or Fair Usage Policy (FUP) and advertisements, the study also demonstrated that this web application provided a free supplementary learning course for the speaking class.